“Principales enfermedades en el cultivo de girasol (Helianthus annuus)”en la Facultad de Ciencias Agropecuarias, Babahoyo - Maldonado Arteaga, Rosa Mercedes (2020)
The work was carried out in the Faculty of Agricultural Sciences of the Technical University of Babahoyo with the aim of obtaining knowledge about the main diseases that are presented in the cultivation of sunflower that is sown and produced in this faculty and identify the symptoms of the main diseases affecting sunflower cultivation in this agricultural area of the province of the Rivers, identify which phytosanitary controls should be performed. Within the general methods that were applied to the study, deductive and inductive methods were used to this research, because the hypothesis was raised and verified throughout the development of research in order to reach the conclusions and recommendations of the work. In the evaluation carried out at the Faculty of Agricultural Sciences it was known that the number of diseases affecting sunflower cultivation among which the following were identified: Moist rot, Verticilosis, Mildew, Leaf spot, Frame rot, Odium they carry out technical measures to be able to control them by carrying out all the phytosanitary practices from the evaluation in the field by the students together with their teachers to the selection of the fungicide to use at the time of the disease. It is important to mention that a programme is carried out of the types of fungicides that will be used in order to avoid the resistance of these pathogens in sunflower culture.